2017
DOI: 10.1089/ten.teb.2016.0446
|View full text |Cite
|
Sign up to set email alerts
|

The Rotator Cuff Organ: Integrating Developmental Biology, Tissue Engineering, and Surgical Considerations to Treat Chronic Massive Rotator Cuff Tears

Abstract: The torn rotator cuff remains a persistent orthopedic challenge, with poor outcomes disproportionately associated with chronic, massive tears. Degenerative changes in the tissues that comprise the rotator cuff organ, including muscle, tendon, and bone, contribute to the poor healing capacity of chronic tears, resulting in poor function and an increased risk for repair failure. Tissue engineering strategies to augment rotator cuff repair have been developed in an effort to improve rotator cuff healing and have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 253 publications
(300 reference statements)
1
14
0
Order By: Relevance
“…Considered to be standard procedure, however positioning of shoulder may be detrimental in osteoporotic bone anchor fixation [12,[28][29][30] Acrominosplasty Removal of acromial spur in response to full thickness tear is commonplace; although optimal timing of acrominoplasty remains unclear [12,[31][32][33][34]] Augmentation Use of patches: material, sizes vary [35][36][37][38][39] Platelet-rich plasma [40][41][42][43] Cell therapy (e.g. mesenchymal stem cells) [44][45][46][47] Post-operative rehabilitation…”
Section: Suture Anchormentioning
confidence: 99%
See 1 more Smart Citation
“…Considered to be standard procedure, however positioning of shoulder may be detrimental in osteoporotic bone anchor fixation [12,[28][29][30] Acrominosplasty Removal of acromial spur in response to full thickness tear is commonplace; although optimal timing of acrominoplasty remains unclear [12,[31][32][33][34]] Augmentation Use of patches: material, sizes vary [35][36][37][38][39] Platelet-rich plasma [40][41][42][43] Cell therapy (e.g. mesenchymal stem cells) [44][45][46][47] Post-operative rehabilitation…”
Section: Suture Anchormentioning
confidence: 99%
“…In developmental biology, Indian Hedgehog (Ihh) and parathyroid hormone (PTH)-related peptide (PTHrP) exist as reciprocal mediators in a feedback loop to control both chondrogenesis and mineralisation of the growth plate and enthesis [38,39]. Taking cues from this, Hettrich et al (2012) injected 114 Sprague-Dawley rats subcutaneously with 10 μg/kg of rhPTH on the day of surgery.…”
Section: Smokingmentioning
confidence: 99%
“…Despite the continuous advancement of rotator cuff repair surgery, non-operative physiotherapy to keep range of movement, rotator cuff and deltoid strength, as well as scapula-stabilizing which utilizes surgical methods to repair the tendon [2], there continues to be increased risk of re-tearing of the tendons after surgical reconstruction [3]. Pathological studies have shown that highly specialized fibro-cartilaginous transition layers between the rotator cuff and the bone cannot regenerate after repair, which leads to patients who cannot be restored to normal function after surgical reconstruction [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Novel techniques are looking at enhancing the tendon tissue regeneration. Such techniques include the use of platelet-rich plasma (PRP), a substance that when injected releases various growth factors that play a role in tissue repair; the use of stem cells, usually mesenchymal stem cells (MSCs), which have the ability to self-renew and differentiate to various tissues [3]; and the use of tissue-engineered approaches which use various scaffolds and patches to augment repair [4,5]. The aim of this review is to critically analyse the new regenerative therapies that have been used recently to facilitate healing following rotator cuff injuries.…”
Section: Introductionmentioning
confidence: 99%